Eksplorasi Teknik Tapestri dan Pewarnaan Serat Lidah Mertua untuk Bahan Alternatif Aksesoris Fesyen - Anjani, Rinta Tri; Haq, Bayyinah Nurrul; Andriana, Yunita Fitra (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2020)
About 60% of synthetic fabric fibers are used in fashion products that threaten the environment because they are difficult to decompose. The exigent condition of the accumulation of waste that does not decompose requires innovation of environmentally friendly materials for the fashion industry. Therefore, to support the use of environmentally friendly materials, this study explores the fibers of the Sanseivera sp. The superiority of the in-laws’ tongue fiber is that it has long fibers, is easy to twist and weave, and is easy to color with natural dyes. The exploration includes processing techniques, namely macramé, tapestry, and other additive exploration; Exploration of the coloring used with natural dyes, namely Secang, Teger, Mango leaves, Avocado, Purple sweet potato, and Mangosteen; and application of exploration results into fashion accessories products. The result is an ideal tapestry technique for the exploration process of fiber materials. Additional materials to strengthen the fiber braid are latex and starch pulp. The exploration of coloring with natural dyes resulted in the Hard - Soft - Warm color range of the Kobayashi color matrix. Exploration application by making bags made of canvas, woven material as a result of technical exploration and coloring is affixed with the squeeze sewing technique.